2021
DOI: 10.3390/biomedicines9121842
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of EZH1 and EZH2 Protein Expression on the Prognosis of Patients with T-Cell Lymphomas

Abstract: T-cell lymphomas are highly heterogeneous and their prognosis is poor under the currently available therapies. Enhancers of zeste homologue 1 and 2 (EZH1/2) are histone H3 lysine-27 trimethyltransferases (H3K27me3). Despite the rapid development of new drugs inhibiting EZH2 and/or EZH1, the molecular interplay of these proteins and the impact on disease progression and prognosis of patients with T-cell lymphomas remains insufficiently understood. In this study, EZH1/2 mutation status was evaluated in 33 monomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…This hypothesis is supported by data from epithelial tumors: in a large cohort of breast cancers, although subtype-dependent overexpression of EZH2 and H3K27m3 overexpression were found, not a single EZH2 mutation could be detected [ 17 ]. Furthermore, in a recent study on T cell lymphomas, again, no correlation between the immunohistochemical expression of H3K27m3/EZH2 and molecular alterations in the EZH2 gene could be identified [ 18 ]. Whether assessing tri-methylation of H3K27 might help to estimate the therapeutic effect of EZH2 - inhibitors remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by data from epithelial tumors: in a large cohort of breast cancers, although subtype-dependent overexpression of EZH2 and H3K27m3 overexpression were found, not a single EZH2 mutation could be detected [ 17 ]. Furthermore, in a recent study on T cell lymphomas, again, no correlation between the immunohistochemical expression of H3K27m3/EZH2 and molecular alterations in the EZH2 gene could be identified [ 18 ]. Whether assessing tri-methylation of H3K27 might help to estimate the therapeutic effect of EZH2 - inhibitors remains to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…So far, contradictory results are available concerning H3K27m3’s or EZH2’s use as surrogate markers [ 17 , 18 ], with a single study confirming H3K27m3’s feasibility in FL [ 9 ]. Further on, H3K27m3 expression has never been used for diagnostic purposes in the differential diagnosis of FL to FH and other B cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…As we and others have shown before, T-cell lymphomas overexpress EZH2, which is correlated to worse survival rates [11,12]. This gives a rationale to evaluate EZH2 inhibition as a potential new therapy of T-cell lymphomas, as a single agent but also in combination with cytotoxic agents, which is currently discussed [13].…”
Section: Introductionmentioning
confidence: 88%
“…A univariable analysis has reported that high EZH2 and H3K27me3 expression are associated with poor overall survival (OS) and progression-free survival (PFS) in patients with T-cell lymphomas [37]. ATL, a T-cell lymphoma with extremely poor prognostic, has an excessive H3K27me3 accumulation [18,38].…”
Section: Emerging Therapies Targeting H3k27me3 Abnormalitiesmentioning
confidence: 99%
“…This could be attributed to the higher activity and plasticity of EZH2, although the details remain unknown. A univariable analysis has reported that high EZH2 and H3K27me3 expression are associated with poor overall survival (OS) and progression-free survival (PFS) in patients with T-cell lymphomas [ 37 ].…”
Section: Emerging Therapies Targeting H3k27me3 Abnormalitiesmentioning
confidence: 99%